PENINGKATAN PENGETAHUAN IBU HAMIL MELALUI EDUKASI PENCEGAHAN ANEMIA - Arnianti; Hastuty, Dewi; Dwi Yanti, Yuniar; Adeliana; Yenni (Jurnal Pengabdian Kepada Masyarakat Pusat Unggulan Iptek Penanggulangan Stunting Berbasis Kesehatan Ibu dan Anak, 2025)
Background: The prevalence of anemia among pregnant women in Indonesia remains high at 48.9%. Anemia during pregnancy not only poses a risk of maternal mortality but also impacts the well-being of both the mother and child. Anemia during pregnancy reflects the socioeconomic well-being of the community and significantly impacts the quality of human resources. Therefore, anemia requires serious attention from relevant parties in implementing interventions and providing quality healthcare services. Objective: This community service initiative aims to enhance pregnant women's knowledge about preventing pregnancy-related anemia. Methods: The activity was conducted by providing education through leaflets, lectures, discussions, and question-and-answer sessions. Knowledge was evaluated through a pretest administered before the education and a post-test administered after the education was conducted. Results: Before the education (pre-test), it was found that 6 pregnant women were in the insufficient category, 4 (27%) had adequate knowledge, and 5 (33%) had good knowledge. In the post-test, 1 (7%) pregnant woman was in the low knowledge category, 3 (20%) had adequate knowledge, and 11 (73%) had good knowledge. Conclusion: Health education on the prevention of anemia during pregnancy can enhance the knowledge of pregnant women.